Multi-omics analysis on the mechanism of the effect of Isatis leaf on the growth performance of fattening sheep - Cao, Zhikun; Yi, Mingliang; Zhou, Jialu; Zhang, Zhiyu; Liu, Zibo; Yang, Chao; Sun, Shixin; Wang, Lei; Ling, Yinghui; Zhang, Zijun; Cao, Hongguo (Frontiers in Veterinary Science, 2024)
This study evaluated the effects of Isatis Leaf (ISL) on the growth performance, gastrointestinal tissue morphology, rumen and intestinal microbiota, rumen, serum and urine metabolites, and rumen epithelial tissue transcriptome of fattening sheep. Twelve 3.5-month-old healthy fattening sheep were randomly divided into two groups, each with 6 replicates, and fed with basal diet (CON) and basal diet supplemented with 80g/kg ISL for 2.5 months. Gastrointestinal tract was collected for histological analysis, rumen fluid and feces were subjected to metagenomic analysis, rumen fluid, serum, and urine for metabolomics analysis, and rumen epithelial tissue for transcriptomics analysis. The results showed that in the ISL group, the average daily gain and average daily feed intake of fattening sheep were significantly lower than those of the CON group (P<0.05), and the rumen ammonia nitrogen level was significantly higher than that of the CON group (P<0.01). The thickness of the reticulum and abomasum muscle layer was significantly increased (P<0.05). At the genus level, the addition of ISL modified the composition of rumen and fecal microorganisms, and the relative abundance of Methanobrevibacter and Centipeda was significantly upregulated in rumen microorganisms, The relative abundance of Butyrivibrio, Saccharofermentans, Mogibacterium, and Pirellula was significantly downregulated (P<0.05). In fecal microorganisms, the relative abundance of Papillibacter, Pseudoflavonifractor, Butyricicoccus, Anaerovorax, and Methanocorpusculum was significantly upregulated, while the relative abundance of Roseburia, Coprococcus, Clostridium XVIII, Butyrivibrio, Parasutterella, Macellibacteroides, and Porphyromonas was significantly downregulated (P<0.05). There were 164, 107, and 77 different metabolites in the rumen, serum, and urine between the ISL and CON groups (P<0.05). The differential metabolic pathways mainly included thiamine metabolism, niacin and nicotinamide metabolism, vitamin B6 metabolism, taurine and taurine metabolism, beta-Alanine metabolism and riboflavin metabolism. These metabolic pathways were mainly involved in the regulation of energy metabolism and immune function in fattening sheep. Transcriptome sequencing showed that differentially expressed genes were mainly enriched in cellular physiological processes, development, and immune regulation. In summary, the addition of ISL to the diet had the effect of increasing rumen ammonia nitrogen levels, regulating gastrointestinal microbiota, promoting body fat metabolism, and enhancing immunity in fattening sheep.